Impact of climate change on agriculture, livestock and living environment in the Southeastern Part of Bangladesh - Mohit, Mohammad Abdul; Eusuf, Muhammad Abum; Humayun, Md Kabir (http://www.jocw.net, 2015)
Bangladesh is one of a disaster prone countriy in the world. About 80% of coastal lands in Bangladesh are annually flooded during the rainy season. It is anticipated that Climate Change through the rise of sea level, will intensify flooding and inundation in the coastal areas of the country. Many geophysical, biological and social systems become imbalanced and are at risk because of climate change. Climate change is a main challenge for agricultural productivity which is anticipated and influenced to affect crop and livestock production by extreme events like drought, floods and storms. It will change the types and frequencies of various crops and livestock, availability of irrigation water supplies and the severity of soil erosion. Climate change risks can be distinguished into two classes. Sudden arrival risks emerge quickly such as flooding or hurricanes and the chronic risks are very slow events that are noticeable by society such as drought or sea level rise. Because of this climate change, social threat focuses on those demographic and socioeconomic factors that increase the impacts of hazard events on local populations (Tierney et al. 2001; Heinz Center 2002). Within the above backdrop, this paper intends to focus the impacts of climate change on agriculture, livestock and living environment of the people in the southeastern part of Bangladesh spesially Jessore, Satkhira, Khulna Mongla Bagerhat and Sundarban.